Implementation of Syncoreblud PT Syncore Indonesia's Digital Marketing Media Strategy in Building the Company's Brand Awareness - Rahmatika Amalia Pawestri; Roostika, Raden Roro Ratna (JURNAL MANAJEMEN MOTIVASI, 2026)
Brand awareness is essential for building consumer trust in a company’s products or services through effective marketing strategies. This study examines the implementation of digital marketing media strategies to build brand awareness at PT Syncore Indonesia, particularly SyncoreBLUD. A qualitative approach was applied through field observations, interviews, and documentation. The findings show that WhatsApp, Instagram, YouTube, Facebook, and the company website are consistently used as digital marketing platforms to strengthen and maintain brand awareness. These platforms support the company’s communication and promotional activities. The results are expected to provide practical insights for developing sustainable digital marketing strategies in the future. Keywords: Digital Marketing Strategy; Social Media Effectiveness; Brand Awareness